Complete mitochondrial genomes of the freshwater mussels Amblema plicata (Say, 1817), Pleurobema oviforme (Conrad, 1834), and Popenaias popeii (Lea, 1857) (Bivalvia: Unionidae: Ambleminae). Issue 3 (2nd July 2020) - Teiga-Teixeira, João; Froufe, Elsa; Gomes-dos-Santos, André; Bogan, Arthur E.; Karatayev, Alexander Y.; Burlakova, Lyubov E.; Aldridge, David C.; Bolotov, Ivan N.; Vikhrev, Ilya V.; Teixeira, Amílcar; Varandas, Simone; Zanatta, David T.; et al.
Abstract: Freshwater mussels are a critically imperiled group of mollusks that play key ecological roles and provide important services to humans. The Ambleminae is the only subfamily of these mussels, endemic to North America. Complete mitogenomes have only been sequenced for two of five tribes of the subfamily. Pleurobema oviforme, Amblema plicata, and Popenaias popeii each belong to tribes Pleurobemini, Amblemini, and Popenaidini, respectively, and have not had published mitogenomes. Thus, this study aims to present the complete mitogenomes for these species, to provide a phylogeny of the Ambleminae and confirm the gene arrangements with representation from each of its tribes. The newly sequenced mitogenomes range from 15, 852 to 15, 993 nucleotides, are composed of 13 PCGs, 22 tRNAs, and two rRNAs and all share the same (UF1) gene order.